2013
DOI: 10.1016/j.jjcc.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-matched lesion-based comparison of midterm outcomes of TAXUS Express and TAXUS Liberté stents for de novo native coronary stenosis

Abstract: The midterm clinical and angiographic outcomes after placement of the new TAXUS-Lib stent for de novo coronary stenosis in a daily practice environment were statistically equivalent compared to the former TAXUS-Exp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…To date only a single study has performed a similar analysis using a metallic DES platform. In their report, Ishikawa et al [13] compared outcomes between the TAXUS Liberte and TAXUS Express stent platform, finding no differences in either patient outcomes or in the incidence of binary ISR. Similar to our study, the difference in the platforms was solely in stent design, with the Liberte stent having a thinner strut and greater spacing to improve homogeneity of drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…To date only a single study has performed a similar analysis using a metallic DES platform. In their report, Ishikawa et al [13] compared outcomes between the TAXUS Liberte and TAXUS Express stent platform, finding no differences in either patient outcomes or in the incidence of binary ISR. Similar to our study, the difference in the platforms was solely in stent design, with the Liberte stent having a thinner strut and greater spacing to improve homogeneity of drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The details of cases involving the use side branch of bifurcation two-stent technique and long stents should be further examined because the platform was quite different between SES (closed-cell based rigid platform) and PES (open-cell based), and the longest standard PES (38 mm) was widely used in daily practice (Table 3). Recently, we reported that the TAXUS Liberté stent did not have a statistically beneficial impact on the mid-term (700-day) angiographic outcomes after placement in a daily practice environment compared to the TAXUS Express stent in a study of more than 1,000 patients with de novo coronary stenosis (21). Thus, although the more uniform neointimal distribution was brought about by the improved diffusion of paclitaxel to the vessel wall due to the thinner TAXUS Liberté stent struts compared to TAXUS Express (1, 2), the angiographic ISR rate of the TAXUS Liberté stent was not significantly different from the other first-generation DESs (Cypher BxV, TAXUS Express) after the baseline adjustment (11,21).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that the TAXUS Liberté stent did not have a statistically beneficial impact on the mid-term (700-day) angiographic outcomes after placement in a daily practice environment compared to the TAXUS Express stent in a study of more than 1,000 patients with de novo coronary stenosis (21). Thus, although the more uniform neointimal distribution was brought about by the improved diffusion of paclitaxel to the vessel wall due to the thinner TAXUS Liberté stent struts compared to TAXUS Express (1, 2), the angiographic ISR rate of the TAXUS Liberté stent was not significantly different from the other first-generation DESs (Cypher BxV, TAXUS Express) after the baseline adjustment (11,21). The difference in the long-term angiographic efficacy (late restenosis and late TLR) between SES and PES should be further examined in future (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishikawa et al (12) reported the results of a comparative study on the clinical outcomes between Taxus Liberte ® (TAXUS-Lib; Boston Scientific, Natick, MA, USA) and Taxus Express ® (TAXUS-Exp; Boston Scientific). They also reported a similar result that the only difference between these two Taxus stents is the stent design, which implies that the Taxus Liberte ® stent has a thinner strut and greater space to improve uniform drug distribution.…”
Section: Discussionmentioning
confidence: 99%